Analisis Wacana Tagline pada Pemilihan Bupati Pandeglang Periode 2020-2024 - Saraswati, Saraswati; Urahmah, Nida (Jurnal Artikula, 2020)
Competition in politics is getting tighter, one of the most important points is marketing techniques or promotional concepts to attract voters. Through appropriate promotional techniques, the target will be netted with more maximum. One of the promotional techniques offered by prospective candidates is to use the tagline as a characteristic and identity.This study analyzed the form of tagline discourse used for promotional concepts using descriptive analysis methods. Documentation techniques and recording techniques. Based on the results of research and discussions that have been described, it can be concluded that the context of discourse on election slogans in Pandeglang Regency in 2020 covers social, cultural, political and religious contexts.The most commonly found context is social context. The types of modes used in discourse on election slogans include the mode of statement, prohibition, warning, solicitation, notice, and command.The most commonly found type of mode is statement. The act of ilokusi contained in the discourse on the most widely found election slogans is a persuasive act of ilokusi.Ko-teks found in the discourse on the election slogan in the form of symbols or signs, images, and colors that accompany the slogan Ko-teks most found is the co-text in the form of color